Opinion on the Transformation of Underachievers in High School Chinese Language Teaching - Zhang, Chenkai; Liu, Zhuneng (Journal of Education and Educational Technologies, 2023)
Deeply understanding and understanding the basic theory of Core Socialist Values is the premise and basis for college students to identify with Core Socialist Values. Faced with various ideological trends, college students lack a certain level of theoretical thinking and the ability to distinguish right from wrong, making it difficult to form scientific values and outlook on life. The ideological and political theory course in colleges and universities is the main channel and important carrier to strengthen the identification and cultivation of college students' Core Socialist Values. Under the background of new media, we must strengthen college students' theoretical cognition of Core Socialist Values. The Core Socialist Values are a main clue that runs through the ideological and political theory courses in colleges and universities. The theoretical connotation of the socialist core value system is reflected to varying degrees in the teaching material system of ideological and political theory courses. For example, adhering to the "guiding ideology of Marxism" and adhering to the "road of Socialism with Chinese characteristics" are mainly reflected in the courses of "Introduction to the Basic Principles of Marxism" and "Outline of China's Modern and Contemporary History", and adhering to the national spirit with patriotism as the core and the Zeitgeist with reform and innovation as the core are mainly reflected in the courses of "Introduction to Maoism and Socialism with Chinese characteristics theoretical system", Adhering to the socialist concept of "eight honors and eight shames" is mainly reflected in the course of "ideological and moral cultivation and legal foundation". The Core Socialist Values are the highly condensed socialist core value system. They are the basic norms and requirements of socialist citizens from the national, social and individual levels. All colleges and universities should attach great importance to the construction of ideological and political theory courses, earnestly promote the Core Socialist Values into the teaching system, into the students' classroom, into the students' minds, reform and innovate from the aspects of teaching content, teaching methods, teaching means, etc., and enhance the pertinence, attractiveness and appeal of teaching. Guide college students to use scientific theoretical knowledge to correctly analyze major theoretical and practical issues, enhance the ability to distinguish right from wrong, form correct Value judgment, and strengthen their political positions and beliefs under the background of new media with various ideological trends and conflicting ideas.